Analysis of Terrain Modelling Methods in the Coastal Zone - Lewicka, Oktawia (Communications - Scientific Letters of the University of Zilina, 2023)
Geospatial data are increasingly used to model the terrain in the coastal zone, in particular in shallow waterbodies (with a depth of up to 1 m). In order to generate a terrain relief, it is important to choose a method for its modelling that will allow it to be accurately projected. Therefore, the aim of this publication is to analyze the terrain modelling methods in the coastal zone. For the purposes of the research, five most popular methods for terrain modelling were described: Inverse Distance Weighted (IDW), Modified Shepard's Method (MSM), Natural Neighbor Interpolation (NNI), kriging and spline. Each of the methods has been described in a uniform way in terms of: the essence of its operation, mathematical expression and application examples. The advantages and disadvantages of each of the methods for terrain modelling are also discussed. It should be stated that the choice of the method for the terrain modelling of a shallow waterbody is not unambiguous, as it depends on the type of data recorded during bathymetric and photogrammetric measurements.
Keywords: terrain modelling; coastal zone; inverse distance weighted (IDW); modified shepard's method (MSM) natural neighbor interpolation (NNI); kriging; spline